Stability of gypseous soils slopes stabilized with cutback asphalt and lime using the finite element method - Abd Hacheem Zuhair; Al-Khyat Sahar; Saeed Khitam Abdulhussein; Fartosy Sabah (Magazine of Civil Engineering)
Gypseous soils are widely distributed all over the world, particularly in Iraq. These soils exhibit unpredictable behaviour including losing strength and collapsing upon wetting. Treatment of gypseous soil is necessary to improve its geotechnical properties and assess its potential applications in engineering practices. Compacted gypseous soil samples stabilized with different binders, including cutback asphalt and lime. Slope stability analysis was performed to determine the factor of safety and analyze the behaviour of the stabilized gypseous soil. ADONIS 3.25, a computer program based on the finite element method, was used to characterize the gypseous soil and to analyze the slope stability by Mohr–Coulomb failure criteria and visco-plastic algorithm. The effects of varying the percentages of binders and the slope angle (H:V) were investigated. A total of thirty numerical analyses were performed. Results of the numerical analysis indicated that the best slope stability was obtained when the gypseous soils stabilized with 4 % cutback asphalt and 3 % lime at a slope angle of 3H:1V. It was also observed that the slope angle has a considerable effect on the safety factor of the slope, such that, the steepest the slope angle – the lowest the safety factor.